Experimental investigation of methane storage on various adsorbents - Keshyap, Jill Priya (2016)
The Adsorption of methane gas on porous materials has attracted attention due to its enhanced adsorptive storage capabilities. Although much research has been done in this field, the adsorption parameters of methane at sub-critical temperatures are scarcely reported in the literature. At higher temperatures, the influence of the microstructure is less important since the repulsive adsorbate-solid interactions dominate. This Final Year Paper (FYP) thus reports an investigation of various microporous materials and the effects of their microstructures on the adsorption uptake levels of methane at subcritical temperatures. The experiments were conducted through a volumetric technique at subcritical temperatures ranging from 90 K to 190 K. The studied materials included (i) metal-organic frameworks (1% Na doped MIL-101 and 1% Li doped MIL-101) and an activated carbon (ii) Maxsorb III. Results demonstrated that due to high surface areas, Maxsorb III obtained the highest gravimetric uptake of methane with an amount of 0.76 kg/kg (at 0.1 bar). Among the MOFs, although the proportion of Li and Na doping retained the microstructural characteristics of the parent MOF, MIL-101, its adsorption capability was not enhanced after the modification. In addition, the adsorption isotherms were fitted with two isotherm models proposed by Langmuir and Toth, with the latter being a better fit due to its accountability of the heterogeneity parameter found in all the adsorbents. Isosteric heats of adsorption were also derived using the Clausius−Clapeyron equation, confirming that increased pore size geometries positively influence the adsorbent-adsorbate interactions of methane and microporous adsorbents.